Lysis - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1998)
"Lysis" by Plato is a dialogue written in the early period of Plato's work. In this philosophical conversation, Socrates encounters young men at a wrestling school and engages them in examining the nature of philia$1 (Ban intimate bond deeper than modern friendship. Through questioning two boys, Lysis and Menexenus, Socrates explores whether true friendship exists between similar people, opposites, or something else entirely. Each promising definition is systematically challenged, leaving the nature of loving friendship mysteriously unresolved. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lysis_(dialogue)
Release date is 1998-12-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Socrates, 470 BC-399 BC; Friendship -- Early works to 1800